Forty Years of Immigrant Segregation in France, 1968-2007: How Different Is the New Immigration? - Jean-Louis Pan Ké Shon; Gregory Verdugo (Institute for the Study of Labor (IZA), 2014)
Analysing restricted access census data, this paper examines the long-term trends of immigrant segregation in France from 1968 to 2007. Similar to other European countries, France experienced a rise in the proportion of immigrants in its population that was characterised by a new predominance of non-European immigration. Despite this, average segregation levels remained moderate. While the number of immigrant enclaves increased, particularly during the 2000s, the average concentration for most groups decreased because of a reduction of heavily concentrated census tracts and census tracts with few immigrants. Contradicting frequent assertions, neither mono-ethnic census tract nor ghettoes exist in France. By contrast, many immigrants live in census tracts characterised by a low proportion of immigrants from their own group and from all origins. A long residential period in France is correlated with lower concentrations and proportion of immigrants in the census tract for most groups, though these effects are sometimes modest.
Keywords: J61; 330; immigration; spatial segregation; France